Nanotechnology as the technology of the future, nanowaste problems - Rudolf, Rebeka; Majerič, Peter; Štager, Vesna; Golub, Doris (Anali PAZU, 2022)
In this paper, we present Nanotechnology, which is a branch of science and engineering focused on materials with at least one dimension below 100 nm. It involves the understanding of materials or processes on the "nano" scale. Nanomaterials, in the form of nanoparticles, nanotubes, nanopyramids, etc., have different properties compared to materials with ordinary dimensions. They have altered physical and chemical properties, which come from the large surface-to-volume ratio. This is reflected in their high surface activity and, because of this, they are useful in various fields (Electronics, Chemistry, Biotechnology, Medicine). Based on this fact, Nanotechnology is a broad term that covers many areas of science, research and technology.